Law diversities for climate change: legal pluralism and climate governance in Indonesia - Tarigan, Muhammad Insan; Hafandi, Raisha (Department of Government Studies, Universitas Muhammadiyah Makassar, 2024)
This study explores global governance dynamics affecting climate change governance in Indonesia, focusing on legal pluralism as a framework for integrating state law, customary law and Islamic law. Considering the context of legal diversity, this study investigates the emergence of models of climate change governance approaches in Indonesia after the 2015 Paris Agreement, specifically examining the consequences of climate change governance on legal mechanisms related to the climate crisis in Indonesia. The study then specifically analyzes ocean-based solutions, highlighting the importance of a focused concentration on climate change governance and legal frameworks in Indonesia. The process of formulating regulations in Indonesia is mainly top-down and neglects to consider the socio-economic rules of the society. As a result, the role of communities at the grassroots level or other social groups is not represented. Therefore, the formulation of Indonesia's NDC policy documents, especially those related to the forest and land use (FOLU) sector, is recommended to increase the inclusiveness of local communities, local governments, and non-governmental organizations. The current paradigm of legal pluralism has the opportunity to improve climate change governance in Indonesia. Climate change policies through international law can be integrated into state law, customary law, and Islamic law in Indonesia in a harmonious way.